2009
DOI: 10.2105/ajph.2007.127464
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Access and Sexually Transmitted Infection Screening Frequency Among At-Risk Massachusetts Men Who Have Sex With Men

Abstract: Clinicians need to assess sexual risk-taking behaviors and more routinely screen for STIs among sexually active men regardless of disclosure of a history of having sex with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 25 publications
4
37
1
Order By: Relevance
“…Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 . Still, such differences may be due to the lack of a standardized period for which the number of partners was computed, varying widely in the literature, or to characteristics like the size of MSM social networks, age, schooling, and social class, factors that may be associated with the number of sexual partners in this sample.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Some RDS studies have found fewer sexual partners than in this study 24,28,39,40 , but our findings are close to other results of RDS studies with MSM 6,25,27,30 . Still, such differences may be due to the lack of a standardized period for which the number of partners was computed, varying widely in the literature, or to characteristics like the size of MSM social networks, age, schooling, and social class, factors that may be associated with the number of sexual partners in this sample.…”
Section: Discussionsupporting
confidence: 89%
“…Reporting a previous syphilis test was statistically associated with HIV infection and syphilis, as in other studies 24,28 , but it can also be associated with risky sexual practices for STI 24,27,28,41 .…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations